The effect of peva 45 steel sheeting thicknesses on PSSDB floor screw stiffness through push-out test - Noor Shuhadah, Saat (2014)
PSSDB is a composite combination Of Profiled Steel Sheeting (PSS) and Dry Board (DB) such as Peva 45 steel sheeting and Primaflex board. It falls under the Industrial Building System. (IBS) category and has many advantages as prefabricated floor panel system. It consists of three important elements which are profiled steel sheeting, dry board and screw by self-drilling and self-tapping. This research is conducted to determine the effect of each sheetmg thickness of Peva 45 on Profiled Steel Sheeting Dry Board (PSSDB) floor panel screw stiffness through push out test Nevertheless, despite the weakness of steel sheetmg which has high strength but low in stiffness that might bring to failure, investigation is made through push out test by using at least two different thickness of Peva 45 sheet Instead, the behavior of this steel-board composite structure through the experiment is recorded and compared with similar previous research. The result from the previous research done showed that the increase of steel sheeting thickness enhanced the strength on PSSDB floor panel screw stiffness From the push-out test, it showed that the screw stiffness increase by 42.03% from 0.69 N/mm to 0.98 N/mm. The maximum force applied increase by only 7.45% from 1.61 kN to :1.73 kN. A hypothesis is draw where the thicker the steel sheet, the stiffer the screw stiffness. Therefore, the objectives are successfully achieved. This research has contributed a better understanding of the influence of steel sheeting thickness towards the screw stiffness.